Pengaruh Gaya Kepemimpinan, Budaya Organisasi Dan Motivasi Kerja Terhadap Kinerja Pegawai (Studi Di Sekretariat Daerah Kabupaten Minahasa Tenggara) - sanyang, Claudy (Universitas Sam Ratulangi, 2019)
The purpose of this study was determine to the effect of Leadership Style, Organizational Culture and Work Motivation towards Employee Performance. This Research done in Regional Secretariat Government of the Southeast Minahasa Regency. This study used quantitative research models of associative. The results of the study can be seen that the variable Leadership Style has a positive and significant effect on Employee Performance. Organizational culture also has a positive and significant effect on Employee Performance. Furthermore, Work Motivation has a positive and significant effect on Employee Performance. So that the Leadership Style, Organizational Culture and Work Motivation simultaneously have a positive and significant effect on Employee Performance. Keywords: Leadership Style, Organizational Culture, Work Motivation, Employee Performanc